(untitled) (Bulletin of criminological association of Ukraine, 2024)
It was determined that control and supervision procedures in the tax field constitute an extensive system. This group includes the procedure for registering taxpayers; administrative procedure of tax audit; the procedure for checking individuals and legal entities by tax authorities within the framework of state control (supervision) and surveillance in the field of pricing. It was noted that the tax audit has the following specific features: firstly, it is a procedure of an initiative nature and is carried out in the presence of the will and interest of the authorized bodies and units of the DPS in order to fulfill their powers within the framework of tax control; secondly, the administrative procedure of the tax audit involves a more intense impact on individuals and legal entities acting as its participants. If, during registration or licensing, the analysis of information about the relevant subject as a whole is mainly carried out, then as part of the inspections, intervention in its operational activities and in-depth study of documentary reporting on its activities is carried out; thirdly, the key task of the administrative procedure of the tax audit is to ensure compliance by individuals and legal entities with tax legislation in the course of conducting their current activities. It has been proven that control and supervisory administrative procedures play an important role for the effective operation of the entire tax sphere, as well as the high-quality and full performance of the tasks and functions assigned to them by tax authorities. These procedures differ in complexity, because they combine a large number of legal, analytical, accounting-monitoring, power- management and other active processes.